Influences of inorganic and organic fertilizers to morphological quality attributes of Shorea macrophylla seedlings in a tropical nursery - Mugunthan Perumal; Mohd Effendi Wasli; Ho Soo Ying (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Perumal M, Wasli ME, Ho SY. 2019. Influences of inorganic and organic fertilizers to morphological quality attributes of Shorea macrophylla seedlings in a tropical nursery. Biodiversitas 20: 2110-2118. Better understanding and implementation of nursery cultural regimes to improve seedling quality with high survival capability and optimal growth potential are one of the pivotal aspects of a successful forest restoration program. An experiment was set to determine the influences of inorganic and organic fertilizers on the morphological quality attributes of Shorea macrophylla (de Vriese) P.S. Ashton seedlings. For seedling production, the pots were filled with a 1:1 mixture of topsoil and sand (v:v), following the standard forest nursery practice. Either a chemical fertilizer (CF, N: P: K = 10: 26: 10) or a blend of 360-day (80% elution of the ingredients at 25°C) controlled-instant release fertilizer (CIRF, N: P: K = 10: 26: 10) or a jellyfish fertilizer (JF, N: P: K = 13.1: 1.7: 0.03) was applied at the rate of 5 g per pot. The findings revealed that the morphological quality attributes of S. macrophylla seedlings treated with JF were significantly higher (P < 0.05) than the seedlings treated with CF and CIRF at the end of nursery growing season. Notwithstanding, in terms of seedling quality indicators, seedlings from all the treatments were fit to the general expectations of a balanced root to shoot ratio values (RS < 2) and the seedlings raised in the nursery were of sub-optimal quality. Consequently, stock quality evaluation requires the integration of both morphological and physiological attributes of seedlings that provides a more effective appraisal of the fitness of seedlings to become established for field planting.